Spinorial field and Lyra geometry - Casana, R.; de Melo, C. A. M.; Pimentel, B. M. (Springer, 2006)
The Dirac field is studied in a Lyra space-time background by means of the classical Schwinger Variational Principle. We obtain the equations of motion, establish the conservation laws, and get a scale relation relating the energy-momentum and spin tensors. Such scale relation is an intrinsic property for matter fields in Lyra background.
Keywords: Lyra geometry; Schwinger Variational Principle; classical fields on non-euclidean manifolds